2014
DOI: 10.1080/09500839.2014.971085
|View full text |Cite
|
Sign up to set email alerts
|

First-principles investigation of bowing parameter in zinc-blendeScxGa1−xN

Abstract: We present first-principles calculations of the structural and electronic properties of binary GaN, ScN and Sc x Ga 1−x N alloys in the zinc-blende structure using pseudopotential plane-wave method within the density functional theory. The alloys are described by considering configurations in 16-atom supercells, corresponding to 2 × 2 × 2 conventional cubic cells. The lattice parameter, bulk modulus, bulk modulus derivation, the energy band gap and bowing parameter are obtained as a function of Sc concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…For the zinc-blende (B3) phase of both binary compounds, it is observed that our results obtained for lattice parameter (a) are very close to the theoretical data. Also, our calculated values of bulk modulus are in good agreement with the results given in the ref [56] and [30] for both binary compounds respectively. Consequently, for concentrations x=0.25, 0.5, and 0.75, none of the measured /theoretical results are available in the literature for comparison.…”
Section: Structural Stabilitysupporting
confidence: 89%
“…For the zinc-blende (B3) phase of both binary compounds, it is observed that our results obtained for lattice parameter (a) are very close to the theoretical data. Also, our calculated values of bulk modulus are in good agreement with the results given in the ref [56] and [30] for both binary compounds respectively. Consequently, for concentrations x=0.25, 0.5, and 0.75, none of the measured /theoretical results are available in the literature for comparison.…”
Section: Structural Stabilitysupporting
confidence: 89%